The power of information and contraceptive choice in a family planning setting in Mexico. Issue 4 (1st August 2000) - Ponce, E C Lazcano; Sloan, N L; Winikoff, B; Langer, A; Coggins, C; Heimburger, A; Conde-Glez, C J; Salmeron, J
Abstract : Objectives: This study measured the effect of information about family planning methods and STD risk factors and prevention, together with personal choice on the selection of intrauterine devices (IUDs) by clients with cervical infection. Methods: We conducted a randomised, controlled trial in which family planning clients were assigned to one of two groups, the standard practice (control) group in which the provider selected the woman's contraceptive and the information and choice (intervention) group. The study enrolled 2107 clients in a family planning clinic in Mexico City. Results: Only 2.1% of the clients had gonorrhoea or chlamydial infections. Significantly fewer women in the intervention group selected the IUD than the proportion for whom the IUD was recommended in the standard care group by clinicians (58.2% v 88.2%, p=0.0000). The difference was even more pronounced among infected women: 47.8% v 93.2% (intervention v control group, p=0.0006). Conclusions: The intervention increased the selection of condoms and reduced the selection of IUDs, especially among women with cervical infections, for whom IUD insertion is contraindicated.